RECENT DEVELOPMENT IN ACOUSTIC ENGINEERING : - You, Kok Yeow, editor; Rashidah @ Siti Saedah Arsat, editor; Forsyth, David Ian, contributors; Goe Samson Andudur, contributors; Juita Junid, contributors; Mohamad Ngasri Dimon, contributors; Nur Amira Muda, contributors; Nur Ayuni Shamsul Bahri, contributors; Rafi'ah Ibrahim, 1987-, contributors; Sharul Kamal Abdul Rahim, contributors; Siti Zaleha Abdul Hamid, contributors (Johor Bahru, Johor : Penerbit UTM Press, 2019)
Includes bibliographical references and index